UNIMAS researcher’s cancer study gains international recognition - Sang Nee, Tan (Universiti Malaysia Sarawak (UNIMAS), 2025)
This UNIMAS news article reports the international recognition received by Dr. Tan Sang Nee for her research in cancer immunology. Her study, published in the Journal of Experimental Medicine (JEM) and selected for both the JEM Cancer Collection and the JEM Clinical Immunology Collection, uncovers how Th1 cells convert into regulatory T cells in the tumor microenvironment via CD39. The article also highlights her media coverage by OncoDaily, recognition by Sigma Xi, and her scientific contributions from postgraduate training at UNIMAS through her postdoctoral work at Tsinghua University.